KONSEP PENDIDIKAN KARAKTER PRESPEKTIF ABDULLAH NASHIH ULWAN - Mohammad Adnan (LP3M STIT Al Urwatul Wutsqo Jombang, 2021)
The reality that is happening at this time, the fulfillment of living facilities, sophisticated technology and increasing social development around us are internal and external factors that affect children's development, besides that developments that occur without any prior screening, so that it has a negative impact on the child's personality. . This is evidenced by the declining morale of the younger generation, the number of acts of deviant behavior of adolescents and students that do not only occur around us. Ironically, moral depravity also occurs in various developed countries, both in the world of education, social, government and entrepreneurship. This shows how bad the current character is. Educators are the most important component in education. Therefore, there are basic qualities that educators must possess, in order to be able to leave a deep mark on the child, and get a positive response from them. Educators should declare their intentions solely for Allah in all their educational work, whether in the form of orders, prohibitions, advice, supervision, or punishment. As stated by 'Abdullah Nashih Ulwan the following: “Sincerity in word and deed is one of the foundations of faith and is a must in Islam. Allah will not accept a deed without doing it sincerely